EFFECTIVENESS OF VIRGIN COCONUT OIL TO XEROSIS IN HEMODIALYSIS PATIENTS AT RST III REKSODIWIRYO PADANG - Ria Desnita; Vivi Syofia Sapardi (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Progressive and irreversible decline in renal function in chronic renal failure requires renal replacement therapy. The most commonly used renal replacement therapy is hemodialysis. Hemodialysis therapy can maintain patient survival and control uremia syndrome. However, uremic toxins cannot be completely resolved by hemodialysis. The uremic toxins that accumulate on the patient's skin can cause xerosis (dry skin). Xerosis can be overcome by providing a moisturizer that has emollient content. One of the natural ingredients that contain emollients and can be used for skin care for hemodialysis patients is virgin coconut oil (VCO).Objective: To determine the effectiveness of virgin coconut oil (VCO) administration against xerosis in patients undergoing hemodialysis.Research Method: This research is a quantitative study with a quasi experimental design approach using one group pre and post test approaches without control group design. The research was conducted in the hemodialysis room RST III Reksodiwiryo Padang. Sampling was done by consecutive sampling technique with a sample size of 11 people. VCO intervention was carried out for 12 days, 2 times a day. Score of xerosis degree before and after intervention was assessed by Overal Dry Skin Score (ODSS).Result: The mean score of degree of xerosis before VCO administration was 3.06 and after VCO administration was 1.39. Based on the t-dependent test statistical test, it was found that the p value = 0.001 (ρ<0.05), meaning that virgin coconut oil was effective in overcoming the problem of xerosis in patients undergoing hemodialysis at RST III Dr. Reksodiwiryo Padang.Conclusion: Virgin coconut oil can be used for skin care to treat xerosis problems in chronic kidney failure patients undergoing hemodialysis.Key words: Hemodialysis, xerosis, virgin coconut oil.